STUDY OF STRUCTURAL, MORPHOLOGICAL AND ELECTRICAL PROPERTIES IN THE (Bi₁.₆Pb₀.₄)(Sr₁.₈Ba₀.₂)Ca₂(Cu₁₋ₓ Gdₓ)₃Oᵧ SUPERCONDUCTORS - LUNG, C.; MARCONI, D.; POP, A. (Studia Universitatis Babeș-Bolyai Physica, 2018)
X-ray powder diffraction (XRD), scanning electron microscopy (SEM) and electrical resistivity measurements are performed to investigate some physical properties of (Bi1.6Pb0.4)(Sr1.8Ba0.2)Ca2(Cu1-xGdx)3Oy superconducting samples fabricated at sintering temperatures of 840 0C and 845 0C and the uniaxial pressures of 196MPa and 392MPa respectively. The samples were prepared by standard solid-state reaction methods. XRD measurements show that the samples obtained at 840 °C contain two phases. With the increase of the sintering temperature at 845 0C, a decrease in the diffraction peaks of the phase 2212 is observed, and with the increase of the pressure at 392MPa this phase falls below 10%. SEM analysis show that the superconductors have a uniform surface, but the size of the granules changes so that the sample sintered at 845 °C and the uniaxial pressure of 392 MPa has the best crystallinity.